Characteristics of Ketapang Leaf Extract and PVA Nano Fibers Using the Electrospinning Method - Sela, Melinia; Anida Chairatunnisa; Rina Aprilia; Rahmanita; Ida Sriyanti; Leni Marlina (Universitas Medan Area, 2024)
The electrospinning method is a method of making nanofibers using the influence of an electric field to produce a jet of electrically charged polymer solution. In this experiment, polyvinyl alcohol (PVA) nanofibers and ketapang leaf extract with various viscosities were made using electrospinning equipment with a static collector. Scanning using an electron microscope (SEM) shows that the morphology of the nanofibers formed looks homogeneous, continuous, and without beads (beads free). The SEM results were analyzed using ImageJ software, which was then carried out using Origin software to determine the fiber diameter. Diameter size distribution with fiber diameter size distribution ranging from 2000 to 8000 nm.